A Usina Hidrelétrica Engenheiro Sérgio Motta e as configurações do Campo Primavera : um estudo sobre o poder simbólico à luz da teoria dos campos, de Pierre Bourdieu - Natt, Elisângela Domingues Michelatto (2011)
The aim of this study was dipped in the quest of understanding the forces that pervade the district of Primavera, São Paulo, Brazil, from the construction of the Engineer Sérgio Motta Dam. In pursuit of the unveiling of the power that permeates the place, it was decided to use as assumption for this research, the Field Theory of Pierre Bourdieu. As we begin our research, however, we were forced to exceed the limits initially set and go in search of information leading up to the implementation process of the plant. Only from the gathering of documentary research an important events were unveiled about the region of the Pontal of the Paranapanema, where is the city of Primavera, was possible could begin the process of designing the field. In order to understand the structures that constituted this field, we traveled n the political place, investigating the circumstances of hydropower generation in Brazil, and realize that you read about the types of housing arising from large generation projects of infrastructure. The focus was the unveiling of symbolic power in the field constituted by Sergio Motta Dam, was necessary to understand the relationships that pervade them, and the incidence of forms of power and violence in the field. From the perspective of structuralism, in methodological and epistemological sense, was able to observe how the agents have structured the field and were structured by it. Know the habitus acquired by these agents, the doxa, which makes them up their positions in the field, and use different forms of capital. The logic that drivers the field and that makes the game so that rules of the game to be possible to survive and the act agents can according to their feel for the game. The research was cross-sectional with a longitudinal perspective, therefore, sought to understand the field as it is set in 2011 at the same time it was necessary to know the history that preceded the field's configuration. In this journey we found that the process of structuring the field and the relations in which agents are entangled, there is the constant exercise of symbolic power, that power veiled and not less concrete or violent. It was concludes that the most violent forms of power that focus on the field, are more subtle and undeclared. They promoters of relations of domination do not allow or encourage reactions and therefore are not perceived, although know and felt in the space of struggles and oppositions that delimits the field, and means that agents are embedded ness.